Thermoeconomic analysis of integrated production of biochar and process heat from quinoa and lupin residual biomass. (March 2018) - Salgado, Mario A. Heredia; Tarelho, Luís A.C.; Matos, Arlindo; Robaina, M.; Narváez, Ricardo; Peralta, Miguel E.
Abstract: Quinoa and lupin are emergent sectors recognized as major promoters of social and economic development in the producer indigenous communities of Ecuador. The associated industrial process requires thermal energy typically produced using subsidized diesel or LPG. This analysis shows that 37.7% of the fuel costs of the analyzed industries are covered by the government in the form of subsidies. Hence, a major risk could be induced into this sector under a subsidy removal scenario. On this regard, the residual biomass generated during quinoa and lupin threshing represents an opportunity for the combined production of biochar for soil amendment and heat as an alternative to replace fossil fuels in the agro-industry sector. This analysis shows that the heat produced during the carbonization of the residual biomass from threshing exceeds the thermal energy required for saponins removal. A positive cash flow was verified in all the considered scenarios. However, the economic performance of the energy system is strongly related to the biochar price rather than the income in result of CO2 emissions trading and fuel costs savings. Furthermore, the current tax incentive represents a subsidy of 39.2% of the initial investment costs to implement a valorization infrastructure. Highlights: 70.7 and 87.5 wt% of the quinoa and lupin crops are wasted during threshing. Quinoa and lupin residual biomass presents high ash, nitrogen and sulfur content. Diesel and LPG utilization can be replaced by the use of residual biomass. 37.7% of the fuel costs are covered by the government in the form of subsidies. Current tax incentive represents a subsidy of 39.2% of the initial investment cost.